Economic assessment of incorporating the hexavalent vaccine as part of the National Immunization Program of Peru - Janice Seinfeld; María Laura Rosales; Alfredo Sobrevilla; Juan Guillermo López Yescas (BMC Health Services Research, 2022)
Abstract Background This study aimed to estimate the economic impact of replacing the current Peruvian primary immunization scheme for infants under 1 year old with an alternative scheme with similar efficacy, based on a hexavalent vaccine. Methods A cost-minimization analysis compared the costs associated with vaccine administration, adverse reactions medical treatment, logistical activities, and indirect social costs associated with time spent by parents in both schemes. A budgetary impact analysis assessed the financial impact of the alternative scheme on healthcare budget. Results Incorporating the hexavalent vaccine would result in a 15.5% net increase in healthcare budget expenditure ($48,281,706 vs $55,744,653). Vaccination costs would increase by 54.1%, whereas logistical and adverse reaction costs would be reduced by 59.8% and 33.1%, respectively. When including indirect social costs in the analysis, the budgetary impact was reduced to 8.7%. Furthermore, the alternative scheme would enable the liberation of 17.5% of national vaccines storage capacity. Conclusions Despite of the significant reduction of logistical and adverse reaction costs, including the hexavalent vaccine into the National Immunization Program of Peru in place of the current vaccination scheme for infants under 1 year of age would increase the public financial budget of the government as it would represent larger vaccine acquisition costs. Incorporating the indirect costs would reduce the budgetary impact demonstrating the social value of the alternative scheme. This merits consideration by government bodies, and future studies investigating such benefits would be informative.